Pembelajaran Matematika yang Berorientasi Multiple Intelligences pada Persamaan dan Pertidaksamaan Linier Satu Variabel - Siska Adilla; Cut Morina Zubainur; Anizar Ahmad (Universitas Syiah Kuala, 2019)
The results of students' mathematics learning are still not optimally. Low learning outcomes due to learning that implemented by teacher not yet accommodate aspects of students intelligence’s. Teachers only focus on the logical mathematical and language intelligences. Whereas every student has another kind of intelligences with different capacities are referred as Multiple Intelligences. Multiple Intelligences should be utilized in the learning process so that students engage actively trying to achieve learning objectives so as to optimize student achievement. Therefore, teachers need to be familiarized implementing of oriented Multiple Intelligences learning. The purpose of this research was to describe the implementation of Multiple Intelligences oriented learning that teachers on the of Linear Equations and Inequalities One Variable. The study also aimed to describes the activities of students during the implementation of Multiple Intelligences oriented learning on Linear Equations and Inequalities One Variable. The study included a math teacher and 24 students of class VII in SMP Negeri 16 Banda Aceh. The implementation data of learning and student activities gathered through observation. The results showed that the enforceability of Multiple Intelligences oriented learning conducted by the teacher in Equality and Linear Inequality One Variable for the first meeting is (84.2%), the third meeting is (89.47%) and the fourth meeting is (89.47%), which include on very high criteria, while the second meeting is (57.84%), include on sufficient criteria. So on the student's activity during the mathematics Multiple Intelligences oriented learning in Equality and Linear Inequality One Variable for the first meeting is (68.4%), and second is (57.89%), which includes the fairly criteria. While the third and the fourth meetings obtained respectively (89.47%), including very high criteria. The implications of this study i.e. teachers need to understand the nature of Multiple Intelligences which is an important aspect to help enable students in an effort to achieve learning objectives.